Wage Inequality in Post-Reform Mexico - Jim Airola; Chinhui Juhn (Institute for the Study of Labor (IZA), 2005)
Using the Mexican Household Income and Expenditure Survey (ENIGH) covering 1984-2000 we analyze wages and employment in Mexico after trade liberalization and domestic reforms. We find that wage inequality and returns to post-secondary schooling increased rapidly during 1984-1994 but stabilized since that period. The end of inequality growth was due to a severe macroeconomic crisis which adversely impacted the better educated, an increase in education levels at the end of the 1990s, and a slowdown in skill demand in the latter half of the 1990s. Between-industry shifts, consistent with trade-based explanations, account for a part of the increase in skill demand during 1984-1994, but these types of movements actually reduced the demand for skill in the latter part of the 1990s. The equalizing impact of trade was offset by within-industry demand shifts which continued to favor more educated workers. The Mexican experience in the 1990s suggests that market-oriented reforms have a sharp initial impact on inequality which dissipates over time. However, the opening of the economy to trade, foreign capital, and global markets also leads to a more long-run increase in the demand for skill.
Keywords: J31; 330; wage inequality; reforms; skill demand